THE RELATIONSHIP BETWEEN MOTIVATION AND SELF-EFFICACY IN TYPE 2 DIABETES MELLITUS PATIENTS IN PUSKESMAS BATUCEPER TANGERANG CITY - Rina Setyoningrum; Karina Megasari Winahyu; Achmad Badawi (Jurnal JKFT, 2016)
Motivation and self-efficacy needed for patients with diabetes mellitus type 2 to improve patient autonomy in managing their illness. This study aimed to identify the relationship between motivation and self-efficacy of patients with diabetes mellitus type 2 in Primary Health Center (Puskesmas) Batuceper Tangerang. The design of this study was an analytic cross-sectional with a sample of 66 patients with diabetes mellitus type 2. The data was collected by a questionnaire and data analysis using Chi-square. The result showed that most respondents have good motivation and as much as 71.2% of respondents have a good self-efficacy as much as 63.6%. bivariate analysis results there is no correlation between motivation and self-efficacy of patients with type 2 diabetes mellitus with p-value 0.281. For further research is expected to look for other factors that affect self-efficacy in patients with diabetes mellitus type 2 in addition to motivation.